Aggressive adenoid cystic carcinoma involving palate extending to maxillary sinus in a young female - Santosh R Patil; Abdalwahab M Alzwiri Zwiri; Krishna A Rao; Ravi Kumar Gudipaneni; Kuraym Khalid Alenazi (Wolters Kluwer Medknow Publications, 2016)
Adenoid cystic carcinoma (ACC) is a rare malignant tumor that affects the head and neck region. It is a malignant tumor arising from minor salivary glands, palate being the most common intraoral location, usually affecting individuals of the fifth decade. This tumor generally has a slow growth rate, and it is often present for several years before the patient seeks treatment. We report a case of extensive ACC involving palate, extending to a maxillary sinus in a young lady.